Colombia's foreign trade and direct investment flows in times of uncertainty. 2015-2021 - Botero-Guzmán, Daniel; Ramírez-Alesón, Marisa (Papeles de Europa, 2024)
The objective of this paper is to describe and analyze the behavior of Colombia's foreign trade and foreign direct investment flows (inward and outward) during the period 2015-2021. It seeks to identify their strengths and weaknesses, with the aim of serving as a basis for decision-making by the agents involved. The information presented is based on data provided by the National Administrative Department of Statistics and the Bank of the Republic of Colombia. The results indicate the persistence and expansion of certain structural characteristics in the exchange of goods and the necessity to confront significant challenges in order to attract investment.
Keywords: Exports; Imports; Foreign Direct Investment; Colombia